Acoustic Radiation Force Impulse Elastography: A Useful Tool for Differential Diagnosis of Thyroid Nodules and Recommending Fine-Needle Aspiration: A Diagnostic Accuracy Study. Issue 42 (October 2015) - Zhang, Yi-Feng; Xu, Jun-Mei; Xu, Hui-Xiong; Liu, Chang; Bo, Xiao-Wan; Li, Xiao-Long; Guo, Le-Hang; Liu, Bo-Ji; Liu, Lin-Na; Xu, Xiao-Hong
Abstract : Abstract: To investigate the diagnostic performance of combined use of conventional ultrasound (US) and elastography, including conventional strain elastography such as elasticity imaging (EI) and acoustic radiation force impulse (ARFI) elastography, and to evaluate their usefulness in recommending fine-needle aspiration (FNA). A total of 556 pathologically proven thyroid nodules were evaluated by US, EI, and ARFI examinations in this study. Three blinded readers scored the likelihood of malignancy for 4 datasets (ie, US alone, US and EI, US and virtual touch tissue imaging [VTI], and US and virtual touch tissue quantification [VTQ]). The diagnostic performances of 4 datasets in differentiating malignant from benign thyroid nodules were evaluated. The decision-making changes for FNA recommendation in the indeterminate nodules or the probably benign nodules on conventional US were evaluated after review of elastography. The diagnostic performance in terms of area under the ROC curve did not show any change after adding EI, VTI, or VTQ for analysis; and no differences were found among different readers; however, the specificity and positive predictive value (PPV) improved significantly after adding VTI or VTQ for analysis in the senior reader. For the indeterminate nodules on US that were pathologically benign, VTQ made correct decision-making changes from FNA biopsy to follow-up in a mean of 82.6% nodules, which was significantly higher than those achieved by EI (46.8%) and VTI (54.4%) (both P < 0.05). With regard to the probably benign nodules on US that were pathologically malignant, EI made the highest correct decision-making change from follow-up to FNA biopsy in a mean of 62.6% nodules (compared with 41.5% on VTQ, P < 0.05). The results indicated that ARFI increases the specificity and PPV in diagnosing thyroid nodules. US combined VTQ might be helpful in reducing unnecessary FNA for indeterminate nodules on US whereas US combined EI is useful to detect the false negative nodules that are probably benign on conventional US.